Agronomic performance of watercress grown in soil under shade cloth - Hirata, Andréia Cristina Silva; Hirata, Edson Kiyoharu (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the agronomic performance of watercress (Rorippa nasturtium‑aquaticum) grown in soil under different shade clothes and full sun in two development cycles (seedling and regrowth). The treatments consisted of watercress grown under 35% black, 35% silver, 35% red, 20% white/silver shade clothes, and under full sun (control), in a randomized complete block design with four replicates. In the first watercress development cycle, there was an increase in fresh weight of up to 59% under shade. The fresh matter from watercress regrowth ranged from 419 g m-2, under full sun, to 3,027.7 g m-2 under the 35% silver shade cloth. Leaf size and canopy height increased under shade. Soil temperature at the 4.0‑cm depth was reduced up to 3°C with the shade clothes, when compared to the full sun treatment. Shade clothes promote greater yield, leaf size, and canopy height in watercress grown in soil, during the seedling and regrowth cycles, with higher yield for the 35% black and 35% silver shade screens.